Citation Analysis of Dissertations Completed at Istanbul University Information and Records Management Department - Fatih Canata; Çağdaş Çapkın; Güleda Doğan; Burcu Sünger; Esra Oynak (Türk Kütüphaneciliği)
The aim of this study is to perform a citation analysis of dissertations completed in Department of Information and Records Management of Istanbul University (DIRMIU) between 1967-2015 and to compare the results with those already done on this topic. For this purpose, completed dissertations in DIRMIU have been determined and data have been gathered from the general characteristics (number of pages, year, advisor and jury members) and references of dissertations. Citation analysis was carried out on the collected data. Additionally, the findings were compared with previous studies on dissertations of Department of Information Management of Hacettepe University (DIMHU) using comparative method. According to the key findings, a total of 120 dissertations were completed in DIRMIU, 91 of which are master’s thesis and 29 of which are doctoral thesis. The 23 advisors and 42 jury members were assigned in these dissertations. Hasan Sacit Keseroğlu, Meral Alpay and Aysel Yontar are among the leading members of the faculty who manage the dissertations most frequently. The most frequently used source types in the dissertations are books (50%) and electronic resources (31%). 69% of these sources are in Turkish and 31% are in other languages. A statistically significant relationship was identified between the types of the thesis and the types of sources and languages used in dissertations. Turkish Librarianship journal and Official Gazette of the Republic of Turkey are the most frequently cited periodicals. The most frequently cited people are Meral Alpay, Jale Baysal, Yasar Tonta, Hasan S. Keseroglu and Aysel Yontar. The half-life of the sources used is 8 years. As a result of the comparison made between DIRMIU and DIMHU, it is seen that the ratio of source type used is similar, the most frequently used periodicals are Turkish Librarianship journal and Official Gazette of the Republic of Turkey, and the half-life is between 8 and 9 years.